Revised criteria for grading resistance against red rot disease of sugarcane - R.P. SINGH, S.K. DUTTAMAJUMDER and (Indian Phytopathology, 2002)
The revised criteria for grading resistance of sugarcane to red rot, caused by Colletotrichum falcatum [Glomerella tucumanensis], are presented. A brief review of the other methods of grading resistance are discussed